The Penta Helix Synergy in Creating DESA BESTARI a Smart Village Marvel - Dida Nurhaida; Ida Busnetty; Tulus Tulus Tahi Hamonangan Tambunan; Nurlida Fatmikasari; Ardiyanto Ardiyanto (Journal of Nonformal Education, 2024)
Rural communities encounter distinct development challenges, necessitating innovative solutions like the smart village initiative. This article delves into the successful implementation of the "Desa Bestari" smart village initiative and the collaborative dynamics among stakeholders within the Penta Helix Model. These stakeholders include representatives from government agencies, local communities, businesses, academic institutions, and mass media. Understanding their perspectives, experiences, and roles in the collaboration process is crucial for gaining insights into the dynamics of the smart village initiative. Employing a qualitative case study approach, the research explores collaboration processes, stakeholder roles, and project outcomes through interviews, observations, and document analysis. Findings underscore the pivotal role of diverse stakeholder collaboration in achieving sustainable rural development. The study elucidates stakeholders' contributions and effective strategies while addressing challenges and lessons learned, offering valuable insights for future smart village projects. This research illuminates the transformative potential of technology-driven rural development initiatives, providing practical guidance for stakeholders and contributing to the understanding of successful smart village implementation.